Reducing Income Inequality and Poverty and Promoting Social Mobility in Korea - Jones, Randall S.. (OECD Publishing, 2014)
To strengthen social cohesion, a top government priority, it is essential to address the labour market roots of inequality by breaking down dualism to reduce the share of non-regular workers and to boost the employment ratio toward the government's 70% target. Education reforms are also important to enhance social mobility. Social welfare programmes should be improved to make them more effective, especially among the elderly, where the relative poverty rate is 49%. In addition, reforms are needed now to develop an effective three-pillar system of retirement income based on the National Pension Scheme, company pensions and individual savings. High household debt also has adverse implications for equity, as well as for growth, as individuals with low income and credit ratings have limited access to financial markets and many are delinquent on their loans. Policies to offer credit to such households and restructure their debt, while limiting moral hazard and developing market-based lending, are essential. This Working Paper relates to the 2014 OECD Economic Survey of Korea (www.oecd.org/eco/economic-survey-korea.htm)
Keywords: Social Issues/Migration/Health; Economics; Korea, Republic of